1990
DOI: 10.1104/pp.92.4.881
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Brittle-2 Gene Effect on Maize Endosperm ADPglucose Pyrophosphorylase Subunits

Abstract: Activity of the enzyme ADPglucose pyrophosphorylase is known to be reduced in maize (Zea mays L.) endosperm mutants at two independent loci, Shrunken-2 (Sh2) and Brittle-2 (Bt2). Spinach leaf ADPglucose pyrophosphorylase has previously been shown to comprise two subunits of 51 and 54 kilodaltons. Antibodies raised to each of the two subunits of spinach leaf ADPglucose pyrophosphorylase were found to cross-react to different bands on Western blots prepared from polyacrylamide gel electrophoresis separated wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 15 publications
7
50
0
Order By: Relevance
“…3B). Consistent with the observation in other plants (Preiss et al, 1989;Okita et al, 1990), these results also indicate that the tomato fruit small subunits share structural homology to the small subunits in spinach leaves and potato tuber, whereas the large subunits are structurally more divergent, as revealed by the inability of the antispinach leaf AGP to cross-react with the tomato fruit large subunits (Fig. 5C).…”
Section: Multiple Forms Of Acp In Tomato Fruitsupporting
confidence: 77%
See 2 more Smart Citations
“…3B). Consistent with the observation in other plants (Preiss et al, 1989;Okita et al, 1990), these results also indicate that the tomato fruit small subunits share structural homology to the small subunits in spinach leaves and potato tuber, whereas the large subunits are structurally more divergent, as revealed by the inability of the antispinach leaf AGP to cross-react with the tomato fruit large subunits (Fig. 5C).…”
Section: Multiple Forms Of Acp In Tomato Fruitsupporting
confidence: 77%
“…Proteolytic degradation of the AGP small subunit was evident during the AGP purification from maize endosperm (Plaxton and Preiss, 1987;Preiss et al, 1989). In the case of barley endosperm AGP, the small subunit was relatively resistant to proteolytic degradation but the large subunit was not, with a half-time for proteolysis at 0 to 4°C on the order of minutes, even in the presence of various protease inhibitors (Kleczkowski et al, 1993).…”
Section: Inhibition Of Protease Activity In Tomato Fruit Crude Extractmentioning
confidence: 95%
See 1 more Smart Citation
“…It is generally believed that there are large and small subunits that are present in equal amounts (17). The small subunits of the enzyme from a range of sources have been found to be closely antigenically related, whereas the large subunits are much less highly antigenically conserved (17,19,20). However, two-dimensional gels have revealed the presence of more than two polypeptides in the enzyme purified from spinach leaf (13) and potato tuber (17).…”
Section: Physical Properties Of the Enzymementioning
confidence: 99%
“…Western blot analyses of maize endosperm crude extracts or of partially purified maize ADPglucose pyrophosphorylase showed that antibodies prepared against the purified spinach leaf ADPglucose pyrophosphorylase 51 kD or 54 kD subunits cross reacted with the 54 kD and 60 kD maize subunits, respectively (21). The cross reaction with the antibody prepared against the spinach leaf 54 kD subunit gave a weaker reaction with the corresponding 60 kD subunit of the maize enzyme than the reaction observed with the anti 51 kD spinach antibody and the corresponding maize endosperm enzyme 54 kD subunit.…”
Section: Structural Analysis Of Adpglucose Pyrophosphorylasementioning
confidence: 99%